Enhanced Incorporation of P into Tensile-Strained GaAs1-yPy Layers Grown by Metal-Organic Vapor Phase Epitaxy at Very Low Temperatures. (1st January 2016) - Guan, Yingxin; Forghani, Kamran; Schulte, K. L.; Babcock, Susan; Mawst, Luke; Kuech, T. F.
Abstract : Metal-organic vapor phase epitaxy (MOVPE) of tensile-strained GaAs1-y Py layers on GaAs substrates was carried out over the temperature range from 380 to 650°C. The P content in the GaAs1-y Py epitaxial layers initially decreases with decreasing growth temperature from 550 to 650°C, while then exhibiting an increase with decreasing growth temperature from 550 to 380°C. Thermodynamic calculations indicate that P incorporation is far from thermodynamic equilibrium at all growth temperatures. Related surface kinetics for the anion incorporation competition are discussed and it is suggested that the P incorporation is assisted by the increased P surface coverage at low growth temperatures. GaAs1-y Py tensile strained layers with layer thickness exceeding the critical thickness exhibit an early stage of strain relaxation by the formation of cracks rather than misfit dislocations.